Examination of the effects of breath hydrogen and methane levels on the EC/IR II. Issue 3 (3rd July 2017) - Kramer-Sarrett, Melissa; Lin, Eugenia; Chua, Kathleen Shari; Pichetshote, Nipaporn; Rezaie, Ali; Pimentel, Mark
ABSTRACT: Fifty patients undergoing hydrogen and methane breath testing at Cedars-Sinai GI Motility Lab were recruited, and consented to having their breath tested for alcohol using the EC/IR II (Intoximeters, Inc., St. Louis). The subjects gave multiple breath samples for alcohol analysis during this controlled study. All subjects had hydrogen in their breath ranging from 1 to 176 parts per million (ppm). Methane was also present in some patients' breath samples (0–107 ppm). In all cases, except for one subject that admitted to heavy drinking the night before, breath alcohol results were 0.000 g/210 L. Based on these findings, breath hydrogen and methane do not have any impact on breath alcohol results with the EC/IR II.